VENTHEART is required for cardiomyocyte specification and function. (25th November 2020) - Jonsson Boezelman, M; Dashi, A; Tan, W; Pan, B; Ilmari, A.M; Tiang, Z; Hartman, R.J.G; Anen, C.G.O; Liu, Z; Wu, J.J; Bin, G; Lim, B; et al.
Abstract: Background: Long noncoding RNAs (lncRNAs) control early stages of cardiac differentiation, however their role in later specification and maturation is still not well explored. Methods and results: We performed single cell RNA-seq for 2, 6 and 12 week-old hESC-CM. Weighted correlation network analysis (WGCNA) identified core genes significantly upregulated, along with a subset of lncRNAs. Importantly, these lncRNAs are highly abundant and unique to human heart. Through independent integrative analysis of genome-wide association studies (GWAS) and expression quantitative trait locus (eQTL) data using human hearts, we also identified a long intergenic noncoding RNA (we call VENTHEART, VHRT) as co-regulated with core cardiac contractile genes, and strongly associated with heart failure. VHRT was highly expressed in MYL2+ hESC-CMs in our single cell dataset, and its locus is antisense and downstream of MYL2. VHRT knockdown (KD) in 6-weeks old hESC-CMs downregulated MYL2 and other key cardiac genes. Patch clamp recordings with VHRT KD cells showed a loss of the ventricular-like action potential. Concordantly, CRISPR-mediated excision of the VHRT locus led to impaired CM sarcomere formation, and loss of CM specification gene programs. VHRT transcript replacement in VHRT-KO cells was however insufficient to rescue the phenotype. Instead, we established by 3C assay, that the VHRT locus loops and interacts with the MYL2 promoter, bearing histone marks characteristic of a super-enhancer. Conclusion: Thus, we conclude that both the VHRT lncRNA transcript and its genomic locus are required for proper CM specification and function, and may play a role in heart failure progression. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): EMBO, Singapore National Research Council